Brown Citrus Aphid Parasitoid, Lipolexis scutellaris Mackauer (Insecta: Hymenoptera: Aphidiidae) - Majorie A. Hoy; Ru Nguyen (EDIS)
The brown citrus aphid, Toxoptera citricida (Kirkaldy), was first detected in Florida in November 1995 in Dade and Broward counties. The brown citrus aphid now has spread throughout the citrus growing region of Florida and could, in future, spread to other citrus-growing regions in the USA. This document is EENY-181, one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.